Chemical composition and acaricidal activity of essential oils from fruits of Illicium verum and rhizomes of Curcuma zedoaria against Dermacentor nitens (Acari: Ixodidae). Issue 6 (1st November 2020) - dos Santos Lima Junior, Gilberto; Campos, Jorge Pedrosa; Monteiro, Caio Márcio de Oliveira; Fiorotti, Jéssica; Júnior, Francisco Eduardo Aragão Catunda; Tomé, Andréia Lima; Perinotto, Wendell Marcelo de Souza
ABSTRACT: This study aimed to determine the chemical composition of essential oils (EOs) from fruits of Illicium verum and rhizomes of Curcuma zedoaria and evaluate the acaricidal activity against Dermacentor nitens, the tropical horse tick. The EOs were characterized by gas chromatography coupled with mass spectrometry analysis. Mostly, the chemical compounds found were ( E )-anethole (88.32%) from I. verum, and 1, 8-cineole (43.49%), curzerenone (13.40%) and camphor (12.29%) from C. zedoaria . The acaricidal activity was evaluated on D. nitens engorged females by Adult Immersion Test (AIT) using 40.0 mg mL −1 of each essential oil. Illicium verum EOs showed a high acaricidal activity (89.6%) on the engorged females and also influenced on larvae hatching percent, while C. zedoaria presented low acaricidal activity (4.9%). The present data provide support for further investigation of I. verum EOs components as novel botanical acaricide to control D. nitens infestations.